New Light on the Bird Phenomenon at Jatinga in North Cachar Hills of Assam - Gupta, Kalyan K. (Indian Forester, 2001)
Every year during autumn-new-moon-phase a large number of birds are attracted by strong unidirectional light sources kept burning on the Jatinga saddle under specific climatic conditions. A five year long study revealed that out of two hundred or more species of birds found in North Cachar Hills, only about fifty species were involved in the phenomenon. Only eight species made up for 75% of the sightings. Most of the individual birds were sub-adults. An analysis of the observed data revealed that night flying birds on autumn migration flight were guided by moon, and in absence of moon were misdirected by any artificial light burning in the desired direction. This was strongly supported by the hypothesis proposed by Baker (1981), that the migratory birds on southward migration, in the Northern Hemisphere, were guided by moon.